SPECT/CT imaging reveals CNS-wide modulation of glymphatic cerebrospinal fluid flow by systemic hypertonic saline - Lilius, Tuomas O.; Rosenholm, Marko; Klinger, Laura; Mortensen, Kristian Nygaard; Sigurdsson, Björn; Mogensen, Frida Lind-Holm; Hauglund, Natalie L.; Nielsen, Malthe Skytte Nordentoft; Rantamäki, Tomi; Nedergaard, Maiken (iScience, 2022)
Intrathecal administration enables central nervous system delivery of drugs that do not bypass the blood-brain barrier. Systemic administration of hypertonic saline (HTS) enhances delivery of intrathecal therapeutics into the neuropil, but its effect on solute clearance from the brain remains unknown. Here, we developed a dynamic in vivo single-photon emission computed tomography (SPECT)/computed tomography (CT) imaging platform to study the effects of HTS on whole-body distribution of the radiolabeled tracer 99mTc-diethylenetriaminepentaacetic acid (DTPA) administered through intracisternal, intrastriatal, or intravenous route in anesthetized rats. Co-administration of systemic HTS increased intracranial exposure to intracisternal 99mTc-DTPA by ∼80% during imaging. In contrast, HTS had minimal effects on brain clearance of intrastriatal 99mTc-DTPA. In sum, SPECT/CT imaging presents a valuable approach to study glymphatic drug delivery. Using this methodology, we show that systemic HTS increases intracranial availability of cerebrospinal fluid-administered tracer, but has marginal effects on brain clearance, thus substantiating a simple, yet effective strategy for enhancing intrathecal drug delivery to the brain. [Display omitted] •We established a SPECT/CT platform for imaging glymphatic drug delivery in vivo•Hypertonic saline (HTS) elevates intracranial availability of CSF-infused 99mTc-DTPA•HTS triples the availability of 99mTc-DTPA in several deep brain regions•HTS has negligible effects on clearance of intrastriatally infused DTPA Drug delivery system; Neuroscience; Small animal imaging